Implementasi Kebijakan Pelestarian Budaya di Kabupaten Lebak dalam Konteks Tradisi Seren Taun - Ezra Kalyla; Nadia Khumairatun Nisa; Muhammad Adjie Akbar; Nathania Aulia Damayanti; Revaldy Putra Razwa; Muhammad Taufik Akbar; Satrio Ramadhan (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the implementation of cultural preservation policies in Lebak Regency in the context of the Seren Taun tradition as part of efforts to maintain local wisdom and sustainable development. The approach used is qualitative with a case study method, through interviews, observations, and documentation studies of local governments, traditional leaders, and the Kasepuhan Citorek community. Data analysis was carried out using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of cultural preservation policies in Lebak has been regulated through Regent Regulation Number 435 of 2022 concerning Regional Cultural Promotion, which emphasizes the importance of indigenous peoples' participation. The implementation of this policy is analyzed using Edwards III's theory, which includes communication, resources, disposition, and bureaucratic structure. The Seren Taun tradition has proven to play an important role in strengthening cultural identity, fostering social solidarity, maintaining food security, and teaching ecological awareness. However, challenges such as budget constraints, low cultural documentation, and shifting values of the younger generation remain major obstacles. This research emphasizes that synergy between the government, customary institutions, and communities is the key to the success of sustainable and inclusive cultural preservation in Lebak Regency.